Non-invasive techniques to study starch structure and starchy products properties. (April 2021) - Teng, Chong; Chen, Da; Wu, Guangfeng; Campanella, Osvaldo H.
Highlights: Molecular modeling allows observing starch structure at the atomic level. Small-angle scattering elucidates amylopectin structure. Solid-state NMR monitors starch type, crystallinity, and reactions. Molecular structure of starch determines their physicochemical properties. Abstract : Starch, a supramolecular architecture assembled mainly by glucose units, is the most common food energy provider for humans and is widely used in food and non-food industries. Unraveling the structure of starch is of vital importance to bridge the gap between its functionality and expanded applications. Many advanced techniques, including molecular modeling, small-angle scattering, and solid-state NMR, are emerging as powerful tools to characterize starch structures at the nano and subnano level. The principles, advantages, and latest progress on structural elucidation of starch comprise the focus of this review. The structure-function relationships of starches from different sources and subjected to different modifications and processing conditions revealed using these techniques are also introduced.